2009
DOI: 10.1051/0004-6361/200912292
|View full text |Cite
|
Sign up to set email alerts
|

Giant planet formation in stellar clusters: the effects of stellar fly-bys

Abstract: Context. The majority of stars in the Galaxy are thought to have formed within stellar clusters, resulting in occasional close encounters between stars during the epoch of planet formation. Encounters between young stars which possess protoplanetary discs will cause significant modification of the disc structure, and perturb any planets forming within the disc. Aims. The primary aim of this work is to examine the effect of parabolic stellar encounters on the evolution of a Jovian-mass giant planet forming with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…Essentially, in clusters with a high binary fraction, exchange encounters are likely to dominate, while in clusters with a low binary fraction, fly-bys are likely play the most important role. Fly-bys can, if they occur during the protoplanetary disc stage, change the frequency of planet formation (Forgan & Rice 2009) or the orbital and physical properties of planets formed (Fragner & Nelson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, in clusters with a high binary fraction, exchange encounters are likely to dominate, while in clusters with a low binary fraction, fly-bys are likely play the most important role. Fly-bys can, if they occur during the protoplanetary disc stage, change the frequency of planet formation (Forgan & Rice 2009) or the orbital and physical properties of planets formed (Fragner & Nelson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To make the model more precise, we should have run the code without the passing star and with the planet on a fixed orbit to give it the time to carve a gap in the disk at its location prior to the stellar flyby. However, as also shown by Fragner & Nelson (2009), a close stellar encounter strongly perturbs the disk, destroying any previous structure present in it. A pre-existing planetary gap would be fully erased by the tidal perturbations of the passing star.…”
Section: Case A: a Single Planet Orbiting At 18 Au From The Starmentioning
confidence: 71%
“…By inspecting the dynamical properties and architecture of planetary systems around stars that were members of clusters, it would be difficult "a posteriori" to distinguish between systems whose evolution was influenced by stellar flybys and those that were not. The influence of stellar flybys will be detectable only on a statistical basis as shown by the modeling of Fragner & Nelson (2009). Many parameters are indeed affecting the behavior of the disk+planet system during the stellar flyby, and they include the initial disk density profile and the architecture of the planetary system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that, in the coplanar case, there were more change of particles between stars when the encounter was prograde. Fragner & Nelson (2009) studied the effect of parabolic encounters in the formation of Jovian-mass planets. They concluded that planets that have been formed after encounters are more massive and also have greater semimajor axes.…”
Section: Introductionmentioning
confidence: 99%